1989
DOI: 10.1111/j.1536-7150.1989.tb02120.x
|View full text |Cite
|
Sign up to set email alerts
|

The General Public and the Art Museum: Case Studies of Visitors to Several Institutions Identify Characteristics of Weir Publics

Abstract: Abstract. From case studies at several art museums, characteristics of several types of museum goers have been identified. Typically museum visitors are in the upper educational, occupational and income groups, younger than the population in general (average age is 34) and active in community and leisure‐time organizations. Frequent visitors do so to be with people, to do something they consider worthwhile, to use surroundings in which they feel comfortable and at ease, to be challenged by new experiences, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…Prince (1990) focused on surveys of visitors to a large number of museums. In the US, Hendon et al (1989) replicated Alt's findings to reveal that the typical museum visitor at the time had a higher education than average, and a higher income than many. These visitors also tended to be younger and more active within their communities than the average American.…”
Section: Studies Of Museum Visitssupporting
confidence: 52%
“…Prince (1990) focused on surveys of visitors to a large number of museums. In the US, Hendon et al (1989) replicated Alt's findings to reveal that the typical museum visitor at the time had a higher education than average, and a higher income than many. These visitors also tended to be younger and more active within their communities than the average American.…”
Section: Studies Of Museum Visitssupporting
confidence: 52%
“…Bourdieu's research influenced several case studies, as well as empirical research, in museums. As Bourdieu predicted, it was repeatedly shown that museum visitors are located within the upper educational, occupational, and income groups (Clarke, 1956;DiMaggio, Useem, & Brown, 1977;Hendon, Costa, & Rosenberg, 1989;Kirchberg, 1996;Merriman, 1991;Peterson, 1992;Tomlinson, 2000). Interestingly, in most studies, education appears to be the strongest determinant of arts involvement (DiMaggio & Useem, 1978;Lopez-Sintas & Garcia-Alvarez, 2002;Zuzanek, 1978).…”
Section: T Stylianou-lambertmentioning
confidence: 87%
“…From this, we can deduce that museum visitors are located mainly in the upper educational, occupational and income groups, as Bourdieu predicted (DiMaggio, Useem and Brown 1977;Hendon, Costa and Rosenberg 1989). …”
Section: Sociological Approachesmentioning
confidence: 93%